Goblet Cell Carcinoid in a Patient with Neurofibromatosis Type 1: A Rare Combination. (4th December 2012) - Gregersen, Tine; Holt, Nanna; Gronbaek, Henning; Vogel, Ida; Jørgensen, Lars J.; Krogh, Klaus
Abstract : Neuroendocrine tumors are rare tumors primarily located in the gastrointestinal tract. Goblet cell carcinoid is a rare subgroup of neuroendocrine tumors located in the appendix. Neurofibromatosis type 1 is an autosomal dominant disorder caused by a mutation in the NF1 gene. Patients with neurofibromatosis type 1 have an increased incidence of typical neuroendocrine tumors, but it is unknown if this is the case with goblet cell carcinoids. We describe a patient with both neurofibromatosis type 1 and goblet cell carcinoid, that according to literature would occur in 0.00017 per million per year. This may suggest a previously unknown association between neurofibromatosis type 1 and goblet cell carcinoids.